The judge bin Shamlah Bahanan and his book Neil Al-Maqsoud in explanation of Sunan abi Daoud from the chapter of what came in answering the invitation to the chapter of the desirability of feast: (transcription and commenting) - Bazarah, Sawsan Ali (Journal of Islamic Sciences, 2023)
This research aims to identify the judge Bahanan, and to explain the desirability of the marriage feast, and conditions of the acceptance of the invitation of the marriage feast and the provisions related to that. The method used in the research is the demonstrative-inferential approach when mentioning hadiths, the analytical-interpretative approach when explaining the meanings of words, the deductive approach when talking about the jurisprudence of hadith, and the historical recursive approach when talking about al-Qadi Bahanan. Where the research was limited to two topics, the first topic is the definition of the judge Bahanan and his book Neil Al-Maqsoud, and the second topic is the provisions of the feast in the light of the opinions of the jurists. The research came to highlight Muslim scholars in general and Yemeni scholars in particular, and to introduce them and their scientific efforts and their service to the prophet`s Sunnah, as well as highlighting the scholars` opinions on the decision of the marriage feast. The research concluded with results, most notably: the judge Bahanan`s interest in his book, Neil Al-Maqsoud, and producing it in a wonderful manner befitting the science it contained. This manuscript is full of various jurisprudential issues and various benefits, such as mentioning the hadith followed by the translation of the chain of narration, attributing the hadith to its sources, mentioning the words included in the narration followed by attribution, judging the hadith, exposing the words contained from the linguistic aspect, clarifying the meanings of strange words, and the narration of the opinions of jurists on the issues contained in the hadith, as it is more like a scholarly, hadith, jurisprudential encyclopedia.